Pelatihan Pemanfaatan Smartboard bagi Guru TK Muslimat Tanjung Qencono untuk Pembelajaran Interaktif Numerasi dan Kognitif Anak Usia Dini - Nina Ikhwati Wahidah; Irma Ayuwanti; Astri Setyawati (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2026)
The use of technology in early childhood learning still faces challenges, particularly due to teachers’ limited ability to operate interactive digital media. This condition affects the optimization of children's numeracy and cognitive development. This community service activity aims to improve the competence of teachers at TK Muslimat Tanjung Qencono in utilizing smartboards as interactive learning media. The implementation methods include socialization, training, hands-on practice, and mentoring. Evaluation is conducted through observation and comparison of abilities before and after the activity. The results show an increase in teacher competence by 82% in operating smartboards and 78% in implementing interactive learning. In addition, children's engagement in learning increases by 75%, as indicated by active participation and positive responses during the learning process. The conclusion shows that smartboard utilization training effectively improves teacher competence and the quality of interactive learning in early childhood education.